Duplication of hypoglossal canal in North Indian human skulls - Fatima, Nafees; Rahman, Shamir; Akhtar, Md. Jawed; Kumar, Vinod (International Journal of Research in Medical Sciences, 2017)
Background: The hypoglossal canal is one among the permanent components of occipital bone of both human being and animal skull, which transmits the twelfth cranial nerve, meningeal branch of ascending pharyngeal artery and emissary veins. This is commonly known as anterior condylar canal. In some cases, this canal is divided by a bony spicule leading to a variant known as double hypoglossal canal. Such partition of hypoglossal canal predisposes the roots of twelfth cranial nerve to entrapment in the occipital bone during ossification which subsequently may leads to an alteration in the tongue movement as well as speech. The objectives of the present study were to obtain the incidence of the variant of double hypoglossal canal in north Indian population especially in Bihar and compare the incidence of such type of variation in skull of different parts of our country as well as various races of the world. Methods: The present study was carried out on 110 undamaged dry adult human crania of unknown age and sex for any variations in the hypoglossal canal or incidence of double hypoglossal canal. Results: We observed 15 cases (13.63%) of double hypoglossal canal in which 8 (7.27%) specimens had unilateral while 7 (6.36%) specimens had bilateral double hypoglossal canal. Double hypoglossal canal was more common in right side. In 5 cases (4.54%) unilateral bony spicules were seen. Conclusions: The study about the hypoglossal canal and its different variation is very important to clinicians, anatomist, forensic experts as well as anthropologists too. The knowledge about the different dimensions of hypoglossal canal is also very essential for neurosurgeons and radiologist for the planning of the surgeries around the posterior cranial fossa for tumors like schwannoma of hypoglossal nerve and treatment of sleep apnea syndrome. Hence the detailed morphometric study of hypoglossal canal will be helpful for the planning of surgical intervention around the base of skull becomes easier and safer.